The Student Facing School and His Own Learning: Some Lines of Research Around the Concept of Involvement - M. Teresa González González (Universidad Autónoma de Madrid, 2016)
Concerns such as school failure, early school dropout, school disengagement and problems of discipline, among others, have been analyzed from different perspectives. At international level, school engagement and disengagement research has highlighted some key points in order to understand these issues. In this paper, some aspects about this broad topic are discussed. A reference to different dimensions of school engagement (behavioural, affective and cognitive) is made, as well as the relevance of building a multidimensional conception of this construct. The last part of the paper alludes to the necessity of approaching the engagement research as an interactive, dynamic, dialectic phenomenon, related to social environments and school cultures and processes.